Analisis Usaha Budidaya Ikan Patin (Studi Kasus Pokdakan Usaha Mandiri) Desa Tangkit Baru Jambi - Arfiana, Bs Monica; Lisna, Lisna; Ramadan, Fauzan (Jurnal Akuakultur Sungai dan Danau, 2026)
POKDAKAN Usaha Mandiri is a fishery cultivation business that was established in 1999 until now. Cultivation activities are carried out by fishery business actors traditionally with homemade feed, farmers have not used much technology and business analysis calculations. Currently, only 30% of ponds are actively operating in cultivation activities. The success of a cultivation business is not only determined by technical factors alone, such as selecting superior seeds and feeding, but also influenced by managerial and economic factors such as calculating production costs, calculating the break-even point, and evaluating the business's financial feasibility. Business analysis plays a strategic role in determining the feasibility, efficiency, and sustainability of catfish cultivation businesses. Therefore, research on the analysis of catfish cultivation businesses in Pokdakan Usaha Mandiri, Tangkit Baru Village, Jambi is important to conduct in order to provide a real picture of business conditions and as a basis for making more rational and sustainable economic decisions. This is expected to help meet the fish needs in Jambi Province. Data collection on Patin fish farmers was carried out intentionally at the Fish Cultivation Group (Pokdakan) Usaha Mandiri which harvested in December in 10 ponds. This research is POKDAKAN data analysis used to determine the financial feasibility of the business is the Revenue Cost of Ratio (RCR), Break Even Point (BEP), and Payback Period (PP). Based on the results of the research, the Patin Fish cultivation business at POKDAKAN Usaha Mandiri, Tangkit Baru Village, was declared financially feasible to be developed. This shows that cultivation activities provide real benefits and have good prospects for